Growth kinetics of small renal mass: Initial analysis of active surveillance registry - Park, Sung-Woo; Lee, Seung Soo; Lee, Dong Hoon; Nam, Jong Kil; Chung, Moon Kee (Investigative and clinical urology, 2017)
To evaluate the clinical safety and natural history of active surveillance (AS) for incidentally diagnosed small renal mass (SRM). We analyzed prospective data for patients who underwent AS for SRM. From 2010 to 2016, 37 SRMs of less than 3 cm were registered. Computed tomography (CT) and magnetic resonance imaging were used for initial diagnosis and CT, ultrasonography, and chest CT were performed at 6-month intervals. If there was no change in size during 2 years, follow-ups were performed annually. If the growth rate was more than 0.5 cm/y, if the diameter was more than 4 cm, or if clinical progression was observed, we regarded it as progression of SRM and recommended active treatment. We compared the growth rate and clinical course of SRM between patients who remained on surveillance and those who had progressed disease. The mean age was 63 years (range, 30-86 years) and the mean diameter was 1.8 cm (range, 0.6-2.8 cm) at diagnosis. The mean follow-up period was 27.3 months (range, 6-80 months) and the average growth rate was 0.2 cm/y (range, 0-1.9 cm/y). Six patients (16.2%) showed progression of SRM. Three patients wanted continuous observation, and partial nephrectomy was performed on 3 other patients. None of the patients had clinical progression, including metastasis. We could delay active treatment for patients with an SRM with scheduled surveillance if the SRM grew relatively slowly. If more long-term AS results are documented for more patients, AS could be an alternative treatment modality for SRM.